2007
DOI: 10.2174/157016207782418452
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing Antibodies in Mucosal Secretions: IgG or IgA?

Abstract: The mucosal immune response to HIV weighs in heavily on the battle against it, as the majority of infections occur via the mucosal route. The antibody response in the mucosae, specifically the genital tract, is characterized by binding and, in some studies, neutralizing HIV-specific IgG and IgA antibodies. Ample evidence, however, points to discrepancies and difficulties in the detection of HIV-specific IgA in HIV-positive subjects, and an even more pronounced divide surfaces in studies done with individuals e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 0 publications
1
39
0
Order By: Relevance
“…immunization, irrespective of the hormonal cycle [3]. Antibodies in genital tract secretions most likely represent both serum derived and locally produced antibodies [14,15] and in contrast to other mucosal tissues, IgG antibodies dominate over IgA antibodies in genital tract secretions (reviewed [16]). …”
Section: Introductionmentioning
confidence: 99%
“…immunization, irrespective of the hormonal cycle [3]. Antibodies in genital tract secretions most likely represent both serum derived and locally produced antibodies [14,15] and in contrast to other mucosal tissues, IgG antibodies dominate over IgA antibodies in genital tract secretions (reviewed [16]). …”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that IgG, rather than IgA, is the most abundant immunoglobulin present in the semen of healthy men. 94,169 Furthermore, the distribution of IgA subclasses indicated the presence of secretory IgA, polymeric IgA and monomeric IgA. 94 Effects of hormones on testicular immune responses Androgens, namely testosterone, have immunosuppressive functions and have been shown to reduce TLR-4 expression in testicular macrophages.…”
Section: Composition Of Semenmentioning
confidence: 99%
“…These observations immediately prompt the need to further investigate the role of IgA in HIV-1 acquisition since it has been significantly associated with mucosal immunity to HIV-1 in several studies of HEPS (188, 190, 192). Moreover, these observations indicate that protection from infection is not necessarily mediated by neutralizing antibodies or robust CTLs as inferred from studies in HEPS, elite controllers, and LTNPs, thus emphasizing the need to re-define correlates of protection, and perhaps keenly study the role of non-neutralizing antibodies in protection versus risk.…”
Section: Correlates Of Immune Protection In the Context Of Vaccine Efmentioning
confidence: 99%